Changes In Soil Aggregate, Bulk Density And Soil Permeability Rate As The Indicators of Soil Crust Process Through The Use Of Chicken Manure And Pam Under Intense Rainfall With One Day Drainage Process - Oteng Haridjaja (Jurnal Ilmu Pertanian, 2007)
-